How do online labour markets facilitate transactions of knowledge-intensive tasks? A service productisation perspective. (14th February 2022) - Zhou, Xiaohao; Mao, Ji-Ye
Despite the increasing importance of online labour markets (OLMs) in service economy, the majority of them transact only simple tasks, without the capability to facilitate knowledge-intensive ones because of their intangibility and subjective nature. Drawing on the service productisation literature, this exploratory case study examines how a leading OLM successfully facilitated a variety of knowledge-intensive tasks such as website and logo design. We developed a process model of service productisation on OLMs, which consists of three stages, service concretisation, process standardisation, and objective assessment. Each stage involves a set of regulating mechanisms for service packaging, transaction process management, and dispute arbitration, respectively, in addition to digital tools, to create product properties for services. We conclude that the regulating mechanisms and digital tools are essential to transact knowledge-intensive tasks on OLMs.